Composite sulfur positive electrode material and preparation method and application thereof

By using a composite structure of carbon-based host material and organic conductive small molecules in the sulfur cathode material of lithium sulfur batteries, the problems of high solubility, easy rupture and poor conductivity of sulfur cathode material in lithium sulfur batteries are solved, and higher specific capacity, cycle stability and rate performance are achieved.

CN119864402AActive Publication Date: 2025-04-22NANKAI UNIV

Patent Information

Application Number
CN202510081097.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-20
Publication Date
2025-04-22
Estimated Expiration
2045-01-20

AI Technical Summary

Technical Problem

The existing lithium-sulfur batteries have problems such as high solubility, easy rupture and differentiation, poor conductivity, poor specific capacity attenuation, poor cycle stability and poor rate performance due to the high solubility of sulfur positive electrode materials.

Method used

A composite sulfur cathode material is used, which consists of a carbon-based host material, sulfur combined on the surface of the carbon-based host material and organic conductive small molecules. Through the synergy between the organic conductive small molecules and the carbon-based host material, it reduces solubility, inhibits volume changes and improves electrical conductivity.

Benefits of technology

The low solubility, stable volume and high conductivity of sulfur cathode material are achieved, and the specific capacity, cycle stability and rate performance of lithium sulfur batteries are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119864402A_ABST
    Figure CN119864402A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of lithium-sulfur battery positive electrode materials, and discloses a composite sulfur positive electrode material and a preparation method and application thereof. The composite sulfur positive electrode material comprises a carbon-based host material as well as sulfur and organic conductive small molecules which are combined on the surface of the carbon-based host material, the mass ratio of the organic conductive small molecules to the sulfur to the carbon-based host material is (0.1-20): (30-90): (10-40). According to the composite sulfur positive electrode material, through the synergistic effect of the organic conductive small molecules and the carbon-based host material, the solubility of the sulfur positive electrode material is reduced, the volume change of the sulfur positive electrode material is inhibited, and the conductivity of the sulfur positive electrode material is improved. Wherein cyano groups in the organic conductive small molecules fix a charge-discharge intermediate polysulfide through electrostatic adsorption, and the porous conductive carbon material serving as a physical barrier can inhibit dissolution and shuttling of the polysulfide; in addition, the composite sulfur positive electrode material containing the metal-modified organic conductive micromolecules also has an effect of rapidly catalyzing a conversion reaction, and high specific capacity, high cycling stability and high rate performance of the lithium-sulfur battery are realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of lithium-sulfur battery positive electrode materials, and in particular to a composite sulfur positive electrode material and a preparation method and application thereof. Background Art

[0002] Lithium-ion batteries are widely used in portable electronic devices, electric vehicles and energy storage due to their light weight, high energy density and no memory effect. However, the theoretical specific capacity of traditional lithium-ion battery electrode materials is limited, and the presence of heavy metal elements brings resource and environmental problems, limiting their large-scale sustainable development. Compared with lithium-ion batteries, lithium-sulfur batteries have a higher theoretical specific capacity and no heavy metals, and are expected to become an important direction for the large-scale development of high-energy-density batteries in the future.

[0003] Lithium-sulfur batteries consist of a sulfur positive electrode and a lithium negative electrode. The sulfur positive electrode undergoes a reversible redox reaction during charging and discharging. After the generation of lithium polysulfide intermediates, Li2S is generated, with a theoretical specific capacity of up to 1672 mAh g -1 , and it is rich in resources, low in cost, and has little pollution; the lithium negative electrode reaction is Theoretical specific capacity 3860mAh g -1 The average output voltage of lithium-sulfur batteries is about 2.1V, and the theoretical energy density is 2600Wh kg -1 , has excellent electrochemical properties, which is expected to bring new breakthroughs and changes to the field of energy storage and help build and improve a sustainable energy system.

[0004] However, existing lithium-sulfur batteries still face a series of challenges. First, the lithium polysulfide intermediates LiPSs produced by the sulfur positive electrode during the charge and discharge process have high solubility in the electrolyte. During the cycle, the positive electrode active material is continuously lost. The LiPSs dissolved in the electrolyte will pass through the diaphragm to the negative electrode side and undergo a series of side reactions on the negative electrode surface, resulting in self-discharge of the battery, attenuation of specific capacity, and poor cycle stability. Secondly, the positive electrode material S8 and its discharge product Li2S have a large density difference. During the charge and discharge process, the electrode will undergo severe volume changes, resulting in the rupture and differentiation of the electrode material and a reduction in the battery cycle life. In addition, the insoluble S8 and Li2S have poor conductivity, and the conversion reaction kinetics of polysulfides are poor. These factors seriously affect the reaction kinetics of the battery and limit its rate performance.

[0005] Based on this, there is an urgent need to develop a composite sulfur positive electrode material. Summary of the invention

[0006] The present application provides a composite sulfur positive electrode material and a preparation method and application thereof, aiming to solve the problems of specific capacity attenuation, poor cycle stability and poor rate performance of existing lithium-sulfur batteries caused by high solubility, easy rupture and differentiation, and poor conductivity of sulfur positive electrode materials.

[0007] In order to achieve the above objectives, the present application adopts the following technical solutions.

[0008] In a first aspect of the present application, a composite sulfur cathode material is provided, comprising a carbon-based host material and sulfur and organic conductive small molecules bound to the surface of the carbon-based host material;

[0009] The mass ratio of organic conductive small molecules, sulfur and carbon-based host materials is (0.1-20):(30-90):(10-40).

[0010] Preferably, the organic conductive small molecule includes at least one of TNCQ, a TNCQ derivative, tetrathiafulvalene or tetracyanoethylene.

[0011] Preferably, the organic conductive small molecule has a chemical structure as shown below:

[0012]

[0013] wherein R1, R2, R3 and R4 are each independently selected from a hydrogen atom, a deuterium atom, a halogen atom, a substituted or unsubstituted C1-C 12 Alkyl or substituted or unsubstituted C2-C 12 alkenyl;

[0014] or,

[0015] The organic conductive small molecule is a complex of TCNQ and tetrathiafulvalene in a mass ratio of (0-20):(0-20);

[0016] or,

[0017] The organic conductive small molecule is a complex of TCNQ and tetracyanoethylene in a mass ratio of (0-20):(0-20).

[0018] Preferably, the organic conductive small molecule has a chemical structure as shown below:

[0019]

[0020] Wherein M is any one or more of Li, Ti, V, Cr, Mn, Fe, Co, Ni, Cu and Zn.

[0021] Preferably, the carbon-based host material includes at least one of graphene, carbon nanotubes, nitrogen-doped graphene, and Ketjen black.

[0022] The second aspect of the present application provides a method for preparing the above-mentioned composite sulfur positive electrode material, comprising:

[0023] S1, dispersing organic conductive small molecules, sulfur powder and carbon-based host materials in an organic solvent, reacting under an inert atmosphere, collecting solid phase products, and obtaining a precursor;

[0024] S2, adding the precursor into a reaction kettle, heating and reacting under an inert atmosphere to obtain a composite sulfur positive electrode material.

[0025] Preferably, the organic solvent includes at least one of carbon disulfide, chloroform, N,N-dimethylformamide, N,N-dimethylacetamide, dimethyl sulfoxide, toluene or ethylene glycol;

[0026] and / or,

[0027] The inert atmosphere is a nitrogen or argon atmosphere.

[0028] Preferably, the reaction temperature in step S1 is 20-50° C., and the reaction time is 12-48 h; the reaction temperature in step S2 is 145-200° C., and the reaction time is 6-36 h.

[0029] The third aspect of the present application provides the use of the above-mentioned composite sulfur positive electrode material in a lithium-sulfur battery.

[0030] In a fourth aspect of the present application, a lithium-sulfur battery is provided, wherein a positive electrode thereof comprises the above-mentioned composite sulfur positive electrode material.

[0031] Compared with the prior art, the beneficial effects of this application are:

[0032] The composite sulfur cathode material of the present application reduces the solubility of the sulfur cathode material, inhibits the volume change of the sulfur cathode material and improves its conductivity through the synergistic effect of organic conductive small molecules and carbon-based host materials. In the composite sulfur cathode material of the present application, the organic conductive small molecules are evenly dispersed on the surface of the porous conductive carbon material, and the cyanide group in the organic conductive small molecules can fix the charge and discharge intermediate polysulfide through electrostatic adsorption, while the porous conductive carbon material can act as a physical barrier to inhibit the dissolution and shuttling of polysulfides; in addition, the composite sulfur cathode material of the present application containing metal-modified organic conductive small molecules also has the function of rapid catalytic conversion reaction, which alleviates the volume change of the composite sulfur cathode material during the charge and discharge process, and further improves its stability and reaction kinetics.

[0033] The composite sulfur positive electrode material of the present application has low solubility, small volume change and excellent conductivity, and is particularly suitable for lithium-sulfur batteries; the lithium-sulfur battery containing the positive electrode active material has high specific capacity, high cycle stability and high rate performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are only some embodiments recorded in the present application, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0035] Figure 1 This is a thermogravimetric analysis test diagram of the organic sulfide prepared in Example 1;

[0036] Figure 2 This is a charge and discharge cycle test diagram of the lithium-sulfur battery 1;

[0037] Figure 3 This is the EIS test diagram of lithium-sulfur battery 1;

[0038] Figure 4 This is a charge and discharge cycle test diagram of lithium-sulfur battery 2;

[0039] Figure 5 This is a charge and discharge cycle test diagram of the lithium-sulfur battery 3;

[0040] Figure 6 This is the charge and discharge cycle test diagram of lithium-sulfur battery D1

[0041] Figure 7 This is the EIS test diagram of lithium-sulfur battery D1. DETAILED DESCRIPTION

[0042] The technical solutions in the embodiments of the present application will be described clearly and completely below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, rather than all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.

[0043] In the following description of this embodiment, the terms "include", "comprising", "having" and "containing" are all open terms, meaning including but not limited to.

[0044] In the following description of this embodiment, the term "and / or" is used to describe the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can represent: A exists alone, B exists alone, and A and B exist at the same time. A and B can be singular or plural. The character " / " generally indicates that the associated objects before and after are in an "or" relationship.

[0045] In the following description of this embodiment, the term "at least one" refers to one or more, and "plurality" refers to two or more. "At least one of the following" or similar expressions refers to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b or c", or "at least one of a, b and c", can all represent: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, c can be single or multiple, respectively.

[0046] The terms used in the embodiments of the present application are only for the purpose of describing specific embodiments, and are not intended to limit the present application. The singular forms "a", "an" and "the" used in the embodiments of the present application and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.

[0047] Those skilled in the art should understand that in the following description of the embodiments of the present application, the order of serial numbers does not mean the order of execution, some or all of the steps can be executed in parallel or sequentially, and the execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of the present application.

[0048] Those skilled in the art will appreciate that the numerical ranges in the embodiments of the present application are to be construed as specifically disclosing each intermediate value between the upper and lower limits of the scope. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present application. The upper and lower limits of these smaller ranges may be independently included or excluded in the scope.

[0049] Unless otherwise specified, the technical / scientific terms used herein have the same meanings as those generally understood by those skilled in the art to which this application belongs. Although this application only describes preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of this application. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials related to the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0050] In a first aspect, the present application provides a composite sulfur cathode material, including a carbon-based host material and sulfur and organic conductive small molecules bound to the surface of the carbon-based host material;

[0051] The mass ratio of organic conductive small molecules, sulfur and carbon-based host materials is (0.1-20):(30-90):(10-40).

[0052] In the present application, the organic conductive small molecule is preferably at least one of TNCQ, a TNCQ derivative, tetrathiafulvalene or tetracyanoethylene, such as TNCQ, a halogen substitute of TNCQ, an alkyl or alkenyl substitute of TNCQ, a complex of TNCQ and a metal ion, and a complex of TNCQ and tetrathiafulvalene (TTF) or a complex of TNCQ and tetracyanoethylene (TCNE).

[0053] Specifically, the organic conductive small molecule has the chemical structure shown below:

[0054]

[0055] wherein R1, R2, R3 and R4 are each independently selected from a hydrogen atom, a deuterium atom, a halogen atom, a substituted or unsubstituted C1-C 12 Alkyl or substituted or unsubstituted C2-C 12 Alkenyl.

[0056] Alternatively, the organic conductive small molecule is a complex of TCNQ and tetrathiafulvalene in a mass ratio of (0-20):(0-20), and its chemical structure is as follows:

[0057]

[0058] Alternatively, the organic conductive small molecule is a complex of TCNQ and tetracyanoethylene in a mass ratio of (0-20):(0-20), and its chemical structure is as follows:

[0059]

[0060] As a more preferred technical solution, the organic conductive small molecule has a chemical structure as shown below:

[0061]

[0062] Wherein M is any one or more of Li, Ti, V, Cr, Mn, Fe, Co, Ni, Cu and Zn.

[0063] In the present application, the carbon-based host material includes at least one of graphene, carbon nanotubes, nitrogen-doped graphene, and Ketjen black.

[0064] The composite sulfur cathode material of the present application reduces the solubility of the sulfur cathode material, inhibits the volume change of the sulfur cathode material and improves its conductivity through the synergistic effect of the organic conductive small molecules and the carbon-based host material. Specifically, in the composite sulfur cathode material of the present application, the cyano group in the organic conductive small molecule can fix the charge and discharge intermediate polysulfide through electrostatic adsorption and improve the conductivity of the cathode; and the carbon-based host material can inhibit the dissolution and shuttling of polysulfide as a physical barrier; under the synergistic effect of the organic conductive small molecule and the carbon-based host material, the specific capacity, cycle stability and rate performance of the lithium-sulfur battery are improved.

[0065] In the preferred embodiment of the present application, the composite sulfur positive electrode material containing metal-modified organic conductive small molecules is selected to have the function of rapid catalytic conversion reaction, and can also alleviate the volume change of the composite sulfur positive electrode material during the charging and discharging process, further improve its stability and reaction kinetics, and thus achieve high specific capacity, high cycle stability and high rate performance of lithium-sulfur batteries.

[0066] In a second aspect, the present application provides a method for preparing the above-mentioned composite sulfur positive electrode material, comprising:

[0067] S1, dispersing organic conductive small molecules, sulfur powder and carbon-based host materials in an organic solvent, reacting under an inert atmosphere, collecting solid phase products, and obtaining a precursor;

[0068] In the present application, the organic solvent provides a reaction site for the reaction principle and promotes the reaction; the organic solvent includes at least one of carbon disulfide, chloroform, N,N-dimethylformamide, N,N-dimethylacetamide, dimethyl sulfoxide, toluene or ethylene glycol.

[0069] In the present application, the inert atmosphere is preferably a nitrogen or argon atmosphere.

[0070] In the present application, the reaction temperature is 20-50°C, the reaction time is 12-48h; the mass ratio of the organic conductive small molecule, sulfur and carbon-based host material is (0.1-20):(30-90):(10-40). After the reaction is completed, the solid phase product is collected by solid-liquid separation, such as drying, filtering, etc.

[0071] S2, adding the precursor into a reaction kettle, heating and reacting under an inert atmosphere to obtain a composite sulfur positive electrode material.

[0072] In the present application, the melt sulfurization treatment is carried out by reacting at 145-200° C. for 6-36 hours. Through the melt sulfurization treatment, sulfur and organic conductive small molecules are infiltrated into the surface of the carbon-based host material to form a composite sulfur positive electrode material with a stable structure.

[0073] The composite sulfur positive electrode material of the present application has low solubility, small volume change and excellent conductivity, and can be used to prepare electrodes for lithium-sulfur batteries. The lithium-sulfur battery containing the positive electrode active material has high specific capacity, high cycle stability and high rate performance.

[0074] The present application also provides a lithium-sulfur battery, the positive electrode of which includes the above-mentioned composite sulfur positive electrode material.

[0075] The lithium-sulfur battery can be prepared by conventional techniques in the art. Specifically, the preparation method of the lithium-sulfur battery of the present application includes:

[0076] The composite sulfur positive electrode material of organic conductive small molecules, conductive additives and adhesives are ground and mixed evenly in N-methylpyrrolidone (NMP) to form a slurry, the slurry is coated on the surface of the carbon-coated aluminum foil current collector, heated and dried to form a positive electrode film, and the positive electrode film is cut into a circle to form a positive electrode sheet; the positive electrode sheet and the negative electrode lithium foil are separated by a diaphragm, an electrolyte is added, and a button-type lithium-sulfur battery is assembled.

[0077] The mass ratio of the composite sulfur positive electrode material, the conductive additive and the binder is (40-80):(50-10):10; the conductive additive can be selected from at least one of SuperP, Ketjen Black or carbon nanotubes; the electrolyte is a solution obtained by dissolving a lithium salt in an organic solvent, which also contains additives. The lithium salt concentration in the electrolyte is 0.5-2.0 mol / L, preferably 1.0 mol / L. The lithium salt is selected from one of lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) or lithium hexafluorophosphate (LiPF6) salts or a mixed salt prepared by mixing several of them in any proportion; the organic solvent is selected from one of 1,3-dioxolane (DOL), ethylene glycol dimethyl ether (DME), 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether (TTE), ethylene carbonate (EC) or dimethyl carbonate (DMC) or a mixed solvent prepared by mixing several of them in any proportion; the additive is selected from one of lithium nitrate (LiNO3), lithium tetrafluoroborate (LiBF4), lithium dioxalatoborate (LiBOB), lithium difluorooxalatoborate (LiDFOB) or an additive prepared by mixing several of them in any proportion.

[0078] The present application is further described below by way of examples.

[0079] Example 1

[0080] This embodiment provides a method for preparing a composite sulfur positive electrode material, comprising:

[0081] 30 mg of TCNQ, 770 mg of sulfur powder and 200 mg of Ketjen black were added to a 50 mL round-bottom flask in sequence, and then 20 mL of carbon disulfide was added, and stirred at 25 °C for 24 hours. After the reaction was completed, the reaction system was allowed to stand, the solvent was removed and the solid product was retained. The product was vacuum dried at 60 °C for 6 hours, transferred to a 100 ml polytetrafluoroethylene reactor, and kept at 155 °C in a vacuum oven for 12 hours. After natural cooling, a composite sulfur positive electrode material was obtained.

[0082] Example 2

[0083] This embodiment provides a method for preparing a composite sulfur positive electrode material, comprising:

[0084] 50 mg of TCNQ, 750 mg of sulfur powder and 200 mg of Ketjen black were added to a 50 mL round-bottom flask in sequence, and then 20 mL of dimethyl sulfoxide was added, and stirred at 25 °C for 24 hours. After the reaction was completed, the reaction system was allowed to stand, the solvent was removed and the solid product was retained. The product was vacuum dried at 60 °C for 6 hours, transferred to a 100 ml polytetrafluoroethylene reactor, and kept at 155 °C in a vacuum oven for 12 hours. After natural cooling, a composite sulfur positive electrode material was obtained.

[0085] Example 3

[0086] This embodiment provides a method for preparing a composite sulfur positive electrode material, comprising:

[0087] 30 mg of F-TCNQ, 750 mg of sulfur powder and 200 mg of Ketjen black were added to a 50 mL round-bottom flask in sequence, and then 20 mL of N,N-dimethylformamide was added and stirred at 25 °C for 24 hours. After the reaction was completed, the reaction system was allowed to stand, the solvent was removed and the solid product was retained. The product was vacuum dried at 60 °C for 6 hours, transferred to a 100 ml polytetrafluoroethylene reactor, and kept at 155 °C in a vacuum oven for 12 hours. After natural cooling, a composite sulfur positive electrode material was obtained.

[0088] Example 4

[0089] This embodiment provides a method for preparing a composite sulfur positive electrode material, comprising:

[0090] 30 mg of F4-TCNQ, 730 mg of sulfur powder and 200 mg of Ketjen black were added to a 50 mL round-bottom flask in sequence, and then 20 mL of carbon disulfide was added, and stirred at 25 °C for 24 hours. After the reaction was completed, the reaction system was allowed to stand, the solvent was removed and the solid product was retained. The product was vacuum dried at 60 °C for 6 hours, transferred to a 100 ml polytetrafluoroethylene reactor, and kept at 155 °C in a vacuum oven for 12 hours. After natural cooling, a composite sulfur positive electrode material was obtained.

[0091] Example 5

[0092] This embodiment provides a method for preparing a composite sulfur positive electrode material, comprising:

[0093] 30 mg of TCNQ-TTF (1:1), 770 mg of sulfur powder and 200 mg of Ketjen black were added to a 50 mL round-bottom flask in sequence, and then 20 mL of carbon disulfide was added. The mixture was stirred at 25 °C for 24 hours. After the reaction was completed, the reaction system was allowed to stand, the solvent was removed and the solid product was retained. The product was vacuum dried at 60 °C for 6 hours, transferred to a 100 ml polytetrafluoroethylene reactor, and kept at 155 °C in a vacuum oven for 12 hours. After natural cooling, a composite sulfur positive electrode material was obtained.

[0094] Example 6

[0095] This embodiment provides a method for preparing a composite sulfur positive electrode material, comprising:

[0096] 30 mg of TCNE, 770 mg of sulfur powder and 200 mg of Ketjen black were added to a 50 mL round-bottom flask in sequence, and then 20 mL of carbon disulfide was added, and stirred at 25 °C for 24 hours. After the reaction was completed, the reaction system was allowed to stand, the solvent was removed and the solid product was retained. The product was vacuum dried at 60 °C for 6 hours, transferred to a 100 ml polytetrafluoroethylene reactor, and kept at 155 °C in a vacuum oven for 12 hours. After natural cooling, a composite sulfur positive electrode material was obtained.

[0097] Example 7

[0098] This embodiment provides a method for preparing a composite sulfur positive electrode material, comprising:

[0099] 30 mg of CuTCNQ, 770 mg of sulfur powder and 200 mg of Ketjen black were added to a 50 mL round-bottom flask in sequence, and then 20 mL of carbon disulfide was added, and stirred at 25 °C for 24 hours. After the reaction was completed, the reaction system was allowed to stand, the solvent was removed and the solid product was retained. The product was vacuum dried at 60 °C for 6 hours, transferred to a 100 ml polytetrafluoroethylene reactor, and kept at 155 °C in a vacuum oven for 12 hours. After natural cooling, a composite sulfur positive electrode material was obtained.

[0100] The composite sulfur cathode material prepared in Example 1 was subjected to thermogravimetric analysis. The thermogravimetric analysis test results are as follows: Figure 1 As shown. Figure 1 It can be seen that the composite sulfur positive electrode material of organic conductive small molecules exhibits a mass retention rate of more than 96% at 200°C and has high thermal stability.

[0101] Example 8

[0102] This embodiment provides a lithium-sulfur battery, wherein the positive electrode active material is the composite sulfur positive electrode material prepared in Embodiment 1, and the preparation method thereof comprises:

[0103] The composite sulfur positive electrode material, Ketjen black and PVDF were mixed in a mass ratio of 8:1:1 to prepare a slurry, the slurry was coated on the surface of the carbon-coated aluminum foil current collector, and the positive electrode film was obtained after drying at 60° C., and the positive electrode disc was obtained after cutting.

[0104] Metal lithium foil was used as the negative electrode, Celgard2325 was used as the separator, LiTFSI was used as the electrolyte, DME and DOL were mixed in a volume ratio of 1:1 as the solvent, and an electrolyte with a molar concentration of 1M was prepared. An additive LiNO3 was added to the electrolyte with a concentration of 2wt%. A button-type (Cion-type 2032) lithium-sulfur battery was assembled in an argon-filled glove box, which was recorded as lithium-sulfur battery 1.

[0105] Example 9

[0106] This embodiment provides a lithium-sulfur battery, wherein the positive electrode active material is the composite sulfur positive electrode material prepared in embodiment 3, and the preparation method thereof comprises:

[0107] The composite sulfur positive electrode material, Super P and PVDF were mixed in a mass ratio of 7:2:1 to prepare a slurry, the slurry was coated on the surface of the carbon-coated aluminum foil current collector, and the positive electrode film was obtained after drying at 60° C., and the positive electrode disc was obtained after cutting.

[0108] Metal lithium foil was used as the negative electrode, Celgard2325 was used as the separator, LiTFSI was used as the electrolyte, DME and DOL were mixed in a volume ratio of 1:1 as the solvent, and the electrolyte with a molar concentration of 1M was prepared. The additive LiNO3 was added to the electrolyte with a concentration of 2wt%. A button-type (Cion-type 2032) lithium-sulfur battery was assembled in a glove box filled with argon gas, which was recorded as lithium-sulfur battery 2.

[0109] Example 10

[0110] This embodiment provides a lithium-sulfur battery, wherein the positive electrode active material is the composite sulfur positive electrode material prepared in Example 7. The preparation method thereof comprises:

[0111] The composite sulfur cathode material, SuperP and PVDF were mixed in a mass ratio of 8:1:1 to prepare a slurry.

[0112] The slurry was coated on the surface of the carbon-coated aluminum foil current collector, and dried at 60° C. to obtain a positive electrode film, which was then cut to obtain a positive electrode disc.

[0113] Metal lithium foil was used as the negative electrode and Celgard2325 as the separator; the electrolyte used was an in-situ polymerized gel electrolyte, and the electrolyte precursor was a DOL solution of LiFSI with a molar concentration of 1.5M. A button-type (Cion-type 2032) lithium-sulfur battery was assembled in an argon-filled glove box. After the battery was assembled, it was heated at 60°C. DOL underwent a ring-opening polymerization reaction under the initiation of LiFSI, and a gel polymer electrolyte was generated in situ. The lithium-sulfur battery obtained in Example 10 is recorded as lithium-sulfur battery 3.

[0114] Comparative Example 1

[0115] This comparative example provides a conventional lithium-sulfur battery, whose positive electrode active material is sulfur. Its preparation method includes:

[0116] Sulfur powder, Super P and PVDF were mixed in a mass ratio of 7:2:1 to prepare a slurry, the slurry was coated on the surface of the carbon-coated aluminum foil current collector, and the positive electrode film was obtained after drying at 60° C., and the positive electrode disc was obtained after cutting.

[0117] Metal lithium foil was used as the negative electrode, Celgard2325 was used as the separator, LiTFSI was used as the electrolyte, DME and DOL were mixed in a volume ratio of 1:1 as the solvent, and the electrolyte with a molar concentration of 1M was prepared. The additive LiNO3 was added to the electrolyte with a concentration of 2wt%. A button-type (Cion-type 2032) lithium-sulfur battery was assembled in a glove box filled with argon gas, which was recorded as lithium-sulfur battery D1.

[0118] The electrochemical performance tests were performed on the lithium-sulfur batteries 1-3 prepared in Examples 8-10 and the lithium-sulfur battery D1 prepared in Comparative Example 1, and the test results are shown in Table 1.

[0119] Table 1 Cycle performance results of lithium-sulfur batteries

[0120] Initial specific capacity 100-cycle specific capacity 200-cycle specific capacity Capacity retention rate Lithium sulfur battery1 <![CDATA[799.7mAhg -1 ]]> <![CDATA[578.4mAhg -1 ]]> <![CDATA[488.2mAhg -1 ]]> 61.0% Lithium sulfur battery 2 <![CDATA[725.9mAhg -1 ]]> <![CDATA[583.1mAhg -1 ]]> <![CDATA[496.1mAhg -1 ]]> 68.3% Lithium sulfur battery 3 <![CDATA[520.4mAhg -1 ]]> <![CDATA[459.8mAhg -1 ]]> <![CDATA[416.7mAhg -1 ]]> 80.1% Lithium sulfur battery D1 <![CDATA[550.9mAhg -1 ]]> <![CDATA[330.3mAhg -1 ]]> <![CDATA[283.6mAhg -1 ]]> 51.5%

[0121] As can be seen from Table 1, compared with ordinary lithium-sulfur batteries, lithium-sulfur batteries containing the composite sulfur positive electrode material of the present application have better cycle performance, and their capacity retention rate is higher than that of ordinary lithium-sulfur batteries after 200 cycles. Among them, the lithium-sulfur battery using the composite sulfur positive electrode material containing metal-modified organic conductive small molecules has a capacity retention rate of up to 80.1% after 200 cycles.

[0122] The test results of lithium-sulfur battery 1 are as follows Figure 2 and Figure 3 As shown. Figure 2 It can be seen that in the test voltage window range of 1.7-2.8V (vs Li / Li + ) within 836mAg -1At the current density (0.5C), the battery’s discharge capacity is 799.7 mAh g -1 , showing higher specific capacity and improved capacity utilization, while also showing higher cycle stability. Figure 3 It can be seen that in the EIS spectrum, the resistance of the two semicircles is relatively low, indicating that the addition of organic conductive small molecules can reduce the surface passivation film resistance and charge transfer resistance of the material.

[0123] The test results of lithium-sulfur battery 2 are as follows Figure 4 As shown. Figure 4 It can be seen that in the test voltage window range of 1.7-2.8V (vsLi / Li + ) within 836mAg -1 At the current density (0.5C), its first cycle discharge capacity can reach 725.9mAh g -1 , showing good charge-discharge cycle stability.

[0124] The test results of lithium-sulfur battery 3 are as follows Figure 5 As shown. Figure 5 It can be seen that in the test voltage window range of 1.7-2.8V (vsLi / Li + ) within 836mAg -1 Under the current density (0.5C), in the 200-cycle charge and discharge cycle test, the capacity retention rate can reach 80.1%, and the charge and discharge cycle stability is very high.

[0125] The test results of the lithium-sulfur battery D1 prepared in Comparative Example 1 are as follows: Figure 6 and Figure 7 As shown. Figure 6 It can be seen that in the test voltage window range of 1.7-2.8V (vs Li / Li + ) within 836mAg -1 At the current density (0.5C), the lithium-sulfur battery D1 showed 550.9mAh g -1 The initial discharge capacity is 283.6 mAh g after 200 cycles. -1 , the capacity retention rate is only 51.4%, the capacity utilization is low and the cycle stability is poor. Figure 7 It can be seen that in the EIS spectrum, the resistance of the two semicircles is relatively large, indicating that the surface passivation film resistance and charge transfer resistance of the material are large, the internal reaction kinetics of the positive electrode are insufficient, and the diffusion of lithium ions in the material structure is poor, which manifests as its poor specific capacity and cycle performance.

[0126] The above test results show that the organic conductive small molecule composite sulfur positive electrode material of the present application is used as a positive electrode active material for lithium-sulfur batteries, and all types of lithium-sulfur batteries containing the positive electrode active material have higher specific capacity, higher cycle stability and higher rate performance.

[0127] Although the present application has been described in detail in general terms and in specific embodiments in this specification, it is obvious to those skilled in the art that some modifications or improvements may be made to the present application. Therefore, these modifications or improvements made without departing from the spirit of the present application are within the scope of protection claimed in the present application.

Claims

1. A composite sulfur positive electrode material, characterized in that: It includes a carbon-based host material and sulfur and an organic conductive small molecule bound to the surface of the carbon-based host material; The mass ratio of organic conductive small molecules, sulfur and carbon-based host materials is (0.1-20):(30-90):(10-40).

2. The composite sulfur cathode material according to claim 1, characterized in that: The organic conductive small molecule includes at least one of TNCQ, a TNCQ derivative, tetrathiafulvalene or tetracyanoethylene.

3. The composite sulfur cathode material according to claim 2, characterized in that: The organic conductive small molecule has a chemical structure as shown below: wherein R1, R2, R3 and R4 are each independently selected from a hydrogen atom, a deuterium atom, a halogen atom, a substituted or unsubstituted C1-C 12 Alkyl or substituted or unsubstituted C2-C 12 alkenyl; or, The organic conductive small molecule is a complex of TCNQ and tetrathiafulvalene in a mass ratio of (0-20):(0-20); or, The organic conductive small molecule is a complex of TCNQ and tetracyanoethylene in a mass ratio of (0-20):(0-20).

4. The composite sulfur positive electrode material according to claim 2, characterized in that: The organic conductive small molecule has a chemical structure as shown below: Wherein M is any one or more of Li, Ti, V, Cr, Mn, Fe, Co, Ni, Cu and Zn.

5. The composite sulfur cathode material according to claim 1, characterized in that: The carbon-based host material includes at least one of graphene, carbon nanotubes, nitrogen-doped graphene, and Ketjen black.

6. The method for preparing the composite sulfur positive electrode material according to any one of claims 1 to 5, characterized in that: include: S1, dispersing organic conductive small molecules, sulfur powder and carbon-based host materials in an organic solvent, reacting under an inert atmosphere, collecting solid phase products, and obtaining a precursor; S2, adding the precursor into a reaction kettle, heating and reacting under an inert atmosphere to obtain a composite sulfur positive electrode material.

7. The preparation method according to claim 6, characterized in that: The organic solvent includes at least one of carbon disulfide, chloroform, N,N-dimethylformamide, N,N-dimethylacetamide, dimethyl sulfoxide, toluene or ethylene glycol; and / or, The inert atmosphere is a nitrogen or argon atmosphere.

8. The preparation method according to claim 6, characterized in that: In step S1, the reaction temperature is 20 to 50°C and the reaction time is 12 to 48 hours; In step S2, the reaction temperature is 145-200° C., and the reaction time is 6-36 hours.

9. Use of the composite sulfur positive electrode material according to any one of claims 1 to 5 in a lithium-sulfur battery.

10. A lithium-sulfur battery, characterized in that: The positive electrode thereof comprises the composite sulfur positive electrode material according to any one of claims 1 to 5.

Citation Information

Patent Citations

  • Electrode active material, lithium ion battery composite positive plate and lithium ion battery

    CN114725379A

  • High-polymer-based intermolecular adsorption-pairing synergistic two-dimensional functional material as well as preparation method and application of high-polymer-based intermolecular adsorption-pairing synergistic two-dimensional functional material

    CN116515058A

  • Sulfur polymer molecular framework composite material as well as preparation method and application thereof

    CN118919729A

  • Organic sulfide, graphene-organic sulfide composite material, active positive electrode material and preparation method and application thereof

    CN119019688A

  • Non-flammable Quasi-Solid Electrolyte and Lithium Secondary Batteries Containing Same

    US20180277913A1

Cited By

  • Application of metal organic polymer in lithium-sulfur battery

    CN121688342A